Clustering User Sentiment Transportasi Online Gojek Dan Grab Dengan Metode K-Means - Dyno Syaiful Annam; Agustia Hananto; Fitria Nurapriani; Tukino Tukino (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2023)
As an online transportation service, people often discuss it by sharing their opinions through various social media platforms, one of which is Google Play reviews. The opinions given by the public regarding online transportation services are diverse. Users provide reviews about the application, and naturally, users will choose an application with good reviews. However, monitoring the opinions of the general public is not easy, given the large volume of data to be processed. Therefore, the researcher aims to obtain accurate and precise information from user reviews of Gojek and Grab using clustering techniques, specifically the K-means method, using the RapidMiner application. The results of the testing of both applications can be summarized as follows: Gojek and Grab receive reviews that are not significantly different, although Grab's reviews are slightly better. The classification using the K-Means method offers a solution to the issue of sentiment analysis in user reviews of online transportation applications.